Preference for Patient -Urologist Gender Similarity and Its Implications for Urology Departments: A Systematic Narrative Review and Thematic Analysis - Tabatabai, Shima; Simforoosh, Nasser (Urology Journal, 2020)
Purpose: To evaluate the evidence that could help health system policy makers to approach the preference for same-gender urologists. Methods: We performed this systematic narrative review according to the PRISMA guidelines. We searched MEDLINE, Web of science, EMBASE, CINAHL and Google Scholar for articles focused on the preference for patient-urologist gender similarity in the male-dominated department from 1999-2019. Finally, a narrative synthesis of studies meeting the inclusion and quality criteria was conducted in accordance with the nature of the evidences. We applied a thematic analysis using inductive approach for synthesizing studies employing heterogeneous research methods and designs. Results: Of 208 titles and abstracts screened, 23 were included and three major themes including reasons, impacts, and implications were identified. Overall, patients with urologic problems prefer same gender urologists and females were more likely to prefer the same gender urologist than males. Many women delays care due to a perceived lack of female urologists. The major identified reasons for the same-gender preference are religious believes, cultural background, emotional relationship, past experiences, and sensitive examinations. The results indicate that the urologists-patients gender similarity improves the quality of primary care. Our review reveled that urologists prefer to perform more same gender-specific procedures. Besides, female urologist and residents perceived to underestimate from their male counterparts. Conclusion: This study could help health system to honor the patient’s preference for same gender urologist. The findings may help medical education and health policy makers to move the male-dominated urology departments towards a culture supportive of female urologists.